A Luminal Loop of Wilson Disease Protein Binds Copper and Is Required for Protein Activity - Köhn, Birgit (Biophys J, 2018)
The copper-transporting ATPase ATP7B is essential for loading of copper ions to copper-dependent enzymes in the secretory pathway; its inactivation results in Wilson disease. In contrast to copper-ion uptake by the cytoplasmic domains, ATP7B-mediated copper-ion release in the Golgi has not been explored yet. We demonstrate here that a luminal loop in ATP7B, rich in histidine/methionine residues, binds reduced copper (Cu(I)) ions, and identified copper-binding residues play an essential role in ATP7B-mediated metal ion release. NMR experiments on short-peptide models demonstrate that three methionine and two histidine residues are specifically involved in Cu(I) ion binding; with these residues replaced by alanines, no Cu(I) ion interaction is detected. Although more than one Cu(I) ion can interact with the wild-type peptide, removing either all histidine or all methionine residues reduces the stoichiometry to one Cu(I) ion binding per peptide. Using a yeast complementation assay, we show that for efficient copper transport by full-length ATP7B, the complete set of histidine and methionine residues in the lumen loop are required. The replacement of histidine/methionine residues by alanines does not perturb overall ATP7B structure, as the localization of ATP7B variants in yeast cells matches that of the wild-type protein. Thus, in similarity to ATP7A, ATP7B also appears to have a luminal “exit” copper ion site.